Demanda por veículos novos no Brasil: uma análise robusta a quebras estruturais - Villela, Bernardo Antunes Maciel (2014)
The automotive sector is fairly representative in the national economy, which motivated this study on the demand for new vehicles in Brazil. The present work discusses an econometric model which allows the calculation of the price, income and credit elasticities on the demand for vehicles in the light of the cointegration theory. Analyzing the period from June 2000 to January 2014, it is possible to observe three structural breaks. These breaks divide the time interval analyzed in four sub-periods, each with its own dynamics. The perception of this fact often overlooked in previous literature is one of the main findings of this work. In fact, very different conclusions would be obtained by considering the entire period without breaks. It is also worth noting that credit has been relevant to the demand in all sub-periods. Therefore, it seems to be effective to implement a policy to boost the automotive sector by encouraging credit. Finally, it is said that in recent history for each 1% reduction in car price, demand has increased in a 30% higher rate. This result corroborates the perception that tax cuts may boost the sale of vehicles.